Estudo comparativo do genoma e do transcriptoma de Phyllosticta citricarpa (fase sexual Guignardia citricarpa) agente da Mancha Preta dos Citros e Phyllosticta capitalensis - Pacheco, Inaiara de Souza [UNESP] (2014)
Citrus black spot (CBP), caused by Phyllosticta citricarpa, is one of the most important citrus disease in the Brazilian citrus industry. However, the mechanisms of pathogenicity of this pathogen during the interactions with their hosts are poorly understood. P. citricarpa is frequently associated with P. capitalensis, which is morphologically similar to the endophytic specie. This feature difficults the differentiation of both species resulting in phytossanitary barriers for in natura fruit exportation. Moreover, their genomes were not fully sequenced yet and there is a lack of knowledge of their transcriptomes in different conditions. Thus, the overall objectives of this work were to evaluate and compare the genome and transcriptome of both species. The total genome sequence was 179,880,616 reads for P. citricarpa and 148,831,020 reads for P. capitalensis assembled in 19,143 and 11,080 contigs, respectively. There were predicted 16,267 ORFs for the pathogenic specie and 14,813 for the endophytic specie. P. citricarpa and P. capitalensis presented very similar amounts of genes. The transcriptomic sequence generated on average 74 billion of reads per biological repeat for each species. There were obtained 3,074 differential expressed transcripts, 2,637 were more expressed in P. citricarpa and 1,097 in P. capitalensis. Transcriptional differences between these species were observed. P. citricarpa showed more expressed genes than P. capitalensis in most analyzed categories. The endophytic specie presented more expressed genes on signaling pathway and adhesion than the pathogenic specie. Additionally, plant-pathogen interaction genes were expressed on P. capitalensis. Thus, the results of genomic and transcriptomic analyses of the P. citricarpa and P. capitalensis contribute to the biology comprehension of these species